The relationship between weight-adjusted-waist index and total bone mineral density in adults aged 20-59 - Guo, Meiqian; Lei, Yi; Liu, Xueqing; Li, Xiang; Xu, Yong; Zheng, Donghui (Frontiers in Endocrinology, 2023)
Introduction According to reports, obesity has a significant impact on bone health. And the weight-adjusted-waist index (WWI), superior to BMI and waist circumference (WC), is a new obesity indicator arising in recent years. This research investigated the relationship between WWI and total bone mineral density (BMD) for adults aged 20 to 59. Methods Using data from the 2011–2018 NHANES, we looked into the independent link between WWI and total BMD as well as its nonlinearity using weighted multiple linear regression and smooth curve fitting. Two-stage linear regression models were employed to calculate the threshold effects. There were additional subgroup analyses and testing for interactions. Results Multiple linear regression studies on a total of 10,372 individuals showed a significant inverse link between WWI and total BMD in adults between 20 and 59 [β = -0.04, 95% CI: (-0.04, -0.03), P<0.0001]. And smoking, race, and chronic kidney disease (CKD) had no significant effect on this negative connection (P for interaction >0.05). In addition, we found a nonlinear relationship between WWI and total BMD in diabetic and CKD patients, for which the saturation point was 11.38 cm/√kg in the CKD patient group and 10.29 cm/√kg in the diabetic patient group. Conclusion Our analysis demonstrated a significant inverse association between WWI and total BMD in adults aged 20-59.